2009
DOI: 10.2214/ajr.08.1152
|View full text |Cite
|
Sign up to set email alerts
|

Scirrhous Metastases to the Gastrointestinal Tract at CT: The Malignant Target Sign

Abstract: OBJECTIVE Our objective was to study the presence of a characteristic appearance of metastatic disease to the gastrointestinal tract on contrast-enhanced CT in patients with known malignancies and to investigate its clinical implications. CONCLUSION Twenty-five patients with scirrhous metastases had a malignant CT target sign. Careful observation and correlation with clinical history are required to differentiate this unique sign from a benign target sign.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Ha et al [19] reported that when the tumour infiltrates all layers, it expands the mucosa, submucosa and serosa rather than the muscularis propria owing to the more tightly packed muscle cells of the latter tissue. Therefore, the muscularis propria is the least thickened hyperattenuating layer in scirrhous metastasis; Gollub et al [14] termed this feature the malignant target sign. Histologically, the gastric muscularis propria, as in other parts of the digestive tract, is thicker and stronger than the mucosa, submucosa or subserosa layers, thus acting as a firm barrier [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ha et al [19] reported that when the tumour infiltrates all layers, it expands the mucosa, submucosa and serosa rather than the muscularis propria owing to the more tightly packed muscle cells of the latter tissue. Therefore, the muscularis propria is the least thickened hyperattenuating layer in scirrhous metastasis; Gollub et al [14] termed this feature the malignant target sign. Histologically, the gastric muscularis propria, as in other parts of the digestive tract, is thicker and stronger than the mucosa, submucosa or subserosa layers, thus acting as a firm barrier [20].…”
Section: Discussionmentioning
confidence: 99%
“…The malignant target sign has been described as a feature of scirrhous metastases to the gastrointestinal tract by Gollub et al [14]. We hypothesised that the hyperattenuating outer layer of the gastric wall may be associated with gastric cancer of the serosa.…”
mentioning
confidence: 85%
“…Initial contrast-enhanced computed tomography (CECT) revealed thickening of the right bladder ( Fig. 1) and rectal walls along with a malignant target sign, which comprised alternating layers of hyper-enhancement in the mucosa, submucosa, and adventitia rectalis with hypo-enhancement in the muscular layers [1]. Thickening of the mesorectal fascia with abnormal tissue stranding and increased perirectal fat density were also evident;…”
Section: Patientmentioning
confidence: 99%
“…outer layer)[1]. With progressive cancer infiltration over time and the eventual development of homogeneous thickening of the intestinal wall, the presence of a malignant target sign can indicate development of ileus[1].…”
mentioning
confidence: 99%
“…Asymmetric thickening is also seen in many small-intestinal malignancies. Small-intestinal lymphoma [21] and small-intestinal metastasis from scirrhous-type gastric primary carcinoma [22] may result in bowel wall thickening that is closer to circumferential and symmetric.…”
Section: Symmetry Of Thickeningmentioning
confidence: 99%